Analisa Kebijakan Pemerintah Terkait Ancaman Pengangguran Pasca Kenaikan Inflasi di Indonesia - Tan Phey Lien; Elvi Juriana; Cheristina; Evelyn; Wenny (JUMBIWIRA : Jurnal Manajemen Bisnis Kewirausahaan, 2022)
A person who has free time, does not have a job and is looking for a job can be said to be an unemployed person. The problem of unemployment in Indonesia will not be exhausted to discuss, unemployment is generally caused by the level of job seekers proportional to the available jobs. This study aims to analyze the factors that affect unemployment in Indonesia. This research uses qualitative research methods, namely by describing various conditions and situations based on existing data. Based on the results that can be concluded, the increase in inflation has resulted in one of the causes of unemployment in Indonesia. Inflation occurred with the highest percentage due to the transportation group with (8.88%). If this is not balanced with people's lifestyles, it will have an impact on unemployment.